K–Ar dating of authigenic minerals in siliciclastic sequences: an example from the south Sanfranciscana Basin (Western Minas Gerais, Brazil) - Maraschin, A.J.; Muzusaki, A.M.; Zwingmann, Horst; Sgarbi, G. (John Wiley and Sons, 2014)
K–Ar dating was applied on authigenic potassic minerals which are abundant in sandstones from the south of the Sanfranciscana Basin, Western Minas Gerais State, central Brazil. The Quintinos Member fluvial sandstones (Três Barras Formation, Areado Group) contain significant amounts of authigenic K-feldspar as microcrystals of adularia and sanidine habits. The ages of these microcrystals cluster into three groups: 106.1 ± 2.2, 89.9 ± 1.9 and 88.8 ± 1.8 Ma (from Albian to Coniacian). The older age of 106.1 ± 2.2 Ma was obtained from the coarse fraction analysed (10–20 µm) that can contain a mixture of detrital potassic minerals (K-feldspar, muscovite, biotite and illite) and different authigenesis of K-feldspar (overgrowths and microcrystals). Thus, only the younger ages were interpreted as precipitation of K-feldspar microcrystals during the Late Cretaceous into the Quintinos Member sandstones. Moreover, these ages can document the formation of microcrystals within a few million years after deposition of the sandstones. The ages of authigenic illite from the Capacete Formation epiclastic sandstones (Mata da Corda Group) range from 88.5 ± 1.9 to 71.5 ± 1.9 Ma (Coniacian–Campanian). These results suggest the timing of the illitization event in these sandstones as well as a synchrony with K-feldspar authigenesis in the Quintinos Member sandstones. These results are well constrained and are in agreement with stratigraphic, biostratigraphic and radiometric ages previously reported for the Sanfranciscana Basin.